2019
DOI: 10.1002/pcr2.10064
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated polymer single crystals and nanowires

Abstract: Conjugated polymer single crystals and nanowires show advantages for the study of intrinsic charge transport in conjugated polymers and achieve high device performance. However, preparation of conjugated polymer single crystals and nanowires, especially donor‐acceptor (D‐A) conjugated polymers, is challenging. In this review, the structural features of conjugated polymers are first described. Then, the mechanism of conjugated polymer crystallization in terms of thermodynamic equilibrium state, nucleation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 174 publications
(306 reference statements)
0
25
0
Order By: Relevance
“…Furan-based biopolymers have received considerable attention in recent years because of their great potential to replace petroleum-based plastics [11]. Organic Semiconductor Single Crystals [58,71,72] are also considered to be an important research topic, given they are "ideal candidates for the construction of high-performance optoelectronic devices/circuits" [55]. In this study, we reported the topochemical polymerization of a furan-based diacetylene (Furan-DA 1).…”
Section: Discussionmentioning
confidence: 99%
“…Furan-based biopolymers have received considerable attention in recent years because of their great potential to replace petroleum-based plastics [11]. Organic Semiconductor Single Crystals [58,71,72] are also considered to be an important research topic, given they are "ideal candidates for the construction of high-performance optoelectronic devices/circuits" [55]. In this study, we reported the topochemical polymerization of a furan-based diacetylene (Furan-DA 1).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other polymers such as polyethylene and polypropylene, which have soft molecular chains that form lamellar crystal structures based on the folding chain model, most conjugating polymers pack into nanofibrillar crystal forms with rigid extended molecular chains. [17] PEDOT nanofibrillar crystals tend to be disordered at a mesoscale and to self-nucleate during removal of the PSS from a PEDOT:PSS complex. In order to obtain nanofibrillar crystals of PEDOT that are ordered over a long range, a template can be used to serve as a nucleating agent to induce the conformational sequence of PEDOT molecular chains along a 1D scale.…”
Section: Preparation Of Pedot Nanofibersmentioning
confidence: 99%
“…The individual nanowire FET exhibited a remarkable hole mobility of up to 24 cm 2 V −1 s −1 (Figure 8d,e), which is the highest reported value in polymer crystal FETs. 100 In addition, the polymer nanowire FETs showed high performance in photoresponsivity and photoswitching. Xiao et al demonstrated a distinct variation of polymer orientation between two thiophene-and thiazolecontained DPP-based polymers in nanowire crystals (Figure 8f).…”
Section: Polymer Crystals and Crystal Structuresmentioning
confidence: 99%